PENGARUH KOMUNIKASI, MOTIVASI, DAN PENEGAKAN DISIPLIN TERHADAP KEPUASAN KERJA PADA PEGAWAI DINAS PENDAPATAN DI KABUPATEN TABANAN - Inten Pratiwi, I Gusti Agung Ayu; Sariyathi, Ni Ketut (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
Factor of human resources (HR) is an element that must be considered by the company as an effort to optimize the service to the community, it is necessary for human resources that have the skills and high professionalism, offset it needs to be supported having regard to employee satisfaction so that the employee's performance can be optimized. This study aimed to determine the effect of communication, motivation, and discipline, employee job satisfaction in the Department of Revenue in Tabanan. The population at the same samples in this study were employees of the Department of Revenue in Tabanan as many as 116 orang.Metode analysis used is multiple linear regression with the F test and t test. Regression analysis showed that communication, motivation, discipline and positive effect on employee job satisfaction Revenue Service in Tabanan. F test and t test showed that the variables of communication, motivation, and discipline positive and significant impact on job satisfaction Revenue Service employee in Tabanan.
Keywords: Communication, Motivation, Discipline Enforcement, Job Satisfaction